Diagnosing unilateral primary aldosteronism – comparison of a clinical prediction score, computed tomography and adrenal venous sampling. (28th December 2013) - Sze, W. C. Candy; Soh, Lip Min; Lau, Jeshen H.; Reznek, Rodney; Sahdev, Anju; Matson, Matthew; Riddoch, Fiona; Carpenter, Robert; Berney, Dan; Grossman, Ashley B.; Chew, Shern L.; Akker, Scott A.; et al.
Summary Context In patients with primary aldosteronism (PA), adrenalectomy is potentially curative for those correctly identified as having unilateral excessive aldosterone production. It has been suggested that a recently developed and published clinical prediction score (CPS) may correctly identify some patients as having unilateral disease, without recourse to adrenal venous sampling. Objective We have applied the CPS to a large cohort of PA patients with defined and documented outcomes. We also incorporated a minor modification to the CPS and a radiological grading score (RGS) into our analysis to assess whether its performance could be augmented. Results A total of 75 patients with a robust diagnosis following bilateral adrenal venous cannulation and/or strictly defined surgical outcome were analysed. Applying the CPS to this group of patients produced a sensitivity of 38·8% and a specificity of 88·5% of correctly identifying unilateral aldosterone production. Using a suggested modification to the CPS, in which different levels of hypokalaemia were given different weightings, the sensitivity rose to 40·8%, with an identical specificity. Using the RGS alone improved sensitivity to 91·7%, but specificity was reduced to 62·5%. Conclusion Applying the recently developed CPS to this cohort of patients, it was not possible to reproduce the 100% specificity reported in the original publication. Using the modified score or incorporating the RGS did not improve its performance. In this cohort, we were unable to show superiority of the CPS over an imaging‐based strategy. CPS may have a role in guiding clinical decision‐making, especially in those whose adrenal venous sampling (AVS) has been unsuccessful.